Dynamics of Land Use Changes Around Toll Exit TollRoad, Batang District - Brian Pradana; Ade Pugara; Bagus Nuari Priambudi (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Development of tollroad infrastructure is the government's priority to increase the mobility of goods and economy in the region. But be aware that there will be changes in land use, especially in the exit toll, It will trigger a new growth centre and land-use changes have occurred in the areas from agricultural land use changed to be non-agriculture land use. This research was located in the Batang Toll exit, Batang Regency with the objective is to determine the dynamics of tollroad development on land-use change. This research will use the GIS method in analyzing land-use change. Result this research in 2016 – 2022, built-up land increased 43,51 Ha and cropland decreased 41,68 Ha. The construction of toll exits has significantly changed in the area on the main route. The positive thing that is obtained is that accessibility between regions becomes easy, both in mobilizing service goods and community connectivity